A Neuroinflammatory Biomarker Profile Associated with Neuropathic Pain in Hansen's Disease: A Systematic Review and Meta-Analysis of S100B, TNF-α, and IL-6 - Dian Rizki Fitria; I Putu Eka Widyadharma; Ni Made Susilawathi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Neuropathic pain (NP) is a severe, chronic complication of Hansen's disease (HD), persisting after antimicrobial therapy and profoundly diminishing quality of life. Its pathophysiology is driven by persistent, complex neuroinflammatory processes within the peripheral nervous system. Circulating biomarkers, especially the glial-derived protein S100B, offer a potential objective window into this underlying pathology. This study aimed to meta-analyze the association between circulating S100B, TNF-α, and IL-6 and the presence of NP in patients with HD. Methods: A systematic search of PubMed, Scopus, and Web of Science databases was conducted for observational studies published between January 2015 and December 2025 that compared biomarker levels in HD patients with and without NP, diagnosed using validated screening instruments. Data from eligible studies were extracted independently, and methodological quality was assessed using the Newcastle-Ottawa Scale. A random-effects meta-analysis was performed to compute the pooled standardized mean difference (SMD) with 95% confidence intervals (CIs) for each biomarker. Results: Seven studies, comprising 812 patients (405 with NP, 407 without NP), met the inclusion criteria. The meta-analysis revealed that serum S100B levels were significantly elevated in HD patients with NP compared to those without (SMD = 1.28, 95% CI [0.95, 1.61], p < 0.001). This finding was accompanied by very high statistical heterogeneity (I² = 78%). Concurrently, the analysis demonstrated significantly higher circulating levels of TNF-α (SMD = 0.89, 95% CI [0.62, 1.16]) and IL-6 (SMD = 0.75, 95% CI [0.48, 1.02]) in the NP group. Conclusion: This meta-analysis establishes a strong statistical association between a distinct neuroinflammatory biomarker profile—characterized by elevated circulating S100B, TNF-α, and IL-6—and the presence of neuropathic pain in Hansen's disease. S100B, as a marker of Schwann cell distress, is a particularly relevant component of this profile. These findings underscore the pivotal role of neuroinflammation in HD-related NP, although the high heterogeneity and non-specific nature of these systemic markers necessitate a cautious interpretation regarding their immediate clinical applicability.